AFLATOXICOSIS IN BROILERS IN KHARTOUM STATE - I. Mursal, Wael; M.Saad, Amir. (Journal of Veterinary Medicine and Animal Production, 2022)
The occurrence and concentration of aflatoxins in broilers feedstuff and livers were investigated and their toxicopathological changes in the liver were described. 100 samples of feed including (Finished Total ration, groundnut cake and dura (sorghum)) and 100 liver samples were collected randomly from 10 poultry (broiler) farms in Khartoum state. After extraction, the aflatoxins were detected using ELISA test. Aflatoxins were detected in all feedstuff samples collected .The concentrations in total finished ration samples (60) varied between 10 and 97 ppb with a mean of 45.5 ppb, groundnut cake samples (20) ranged between 84 and 109 ppb with a mean of 91.4 ppb and in dura (sorghum) samples (20) varied between 7 and 10 ppb with a mean of 9.3 ppb. Seventeen out of one hundred liver samples examined were positive for aflatoxins residues and the concentrations varied between 2 and 12 ppb with a mean of 4.9 ppb. The affected liver showed hepatomegaly, paleness, wide areas of hemorrhages and necrosis. Histopathology revealed congestion of central vein, hemorrhages, vacuolar degeneration, necrosis and nodular lymphoid infiltration.